Risk Prediction and Assessment of Intervention, Re-education and Reintegration of Juvenile Offenders: Development and Psychometric Properties of the PREVI-A - Graña Gómez, José Luis; Ronzón-Tirado, Román; Andreu Rodríguez, José Manuel; de la Peña Fernández, María Elena (Frontiers in Psychology, 2022)
This paper proposes and analyzes the psychometric properties of the PREVI-A scale (Predicción del Riesgo y Valoración de la Intervención en la ARRMI––Risk Prediction and Intervention Assessment in the ARRMI). It describes the process of item development, the factorial structure of the scale, reliability, evidence of validity and diagnostic performance with regard to recidivism risk in juvenile offenders. The sample was made up of 212 juvenile offenders held at detention centers run by the Madrid Agency for Reeducation and Reintegration of Juvenile Offenders, a regional government body. Statistical analyses were used to corroborate the theoretical factorial structure of the PREVI-A, which consists of six risk/protection dimensions (64 items) based on the Risk-Needs-Responsivity Model, and to obtain empirical support for the reliability and validity of PREVI-A as a tool to assess the risk of recidivism by juvenile offenders in Spain.